Insulin Resistance is a Risk Factor for Early Miscarriage and Macrosomia in Patients With Polycystic Ovary Syndrome From the First Embryo Transfer Cycle: A Retrospective Cohort Study - Chen, Yuanhui; Guo, Jiayu; Zhang, Qingwen; Zhang, Cuilian (Frontiers in Endocrinology, 2022)
Objective: To explore the effect of insulin resistance on pregnancy outcomes in patients with polycystic ovary syndrome (PCOS) from the first embryo transfer cycle. Design: Single-center, retrospective, observational cohort study. Patients: Women with PCOS for the first embryo transfer. Main Outcome Measures Early miscarriage rate, macrosomia rate. Results: With increased HOMA-IR, the early miscarriage rate (7.14%, 13.21%, 16.22%, respectively; P=0.039), macrosomia rate (5.78%, 11.79%, 17.58%, respectively; P=0.026) and the incidence of gestational diabetes (GDM) (10.00%, 14.50%, 25.67% respectively; P=0.002) significantly increased, while the live birth rate markedly decreased (63.03%, 55.27%, 47.88%, respectively; P=0.004). No significant difference was found in clinical pregnancy rate, late miscarriage rate, low birthweight rate and baby gender ratio (all P>0.05). After adjusting for confounding factors, HOMA-IR was an independent risk factor of early miscarriage rate and macrosomia rate. Conclusion: Insulin resistance was an independent risk factor for early miscarriage and macrosomia in PCOS patients during the first embryo transfer cycle. It is essential to give more attention before and after pregnancy for PCOS women with high HOMA-IR. Key words insulin resistance; polycystic ovarian syndrome; early miscarriage; macrosomia; in vitro fertilization